2004
DOI: 10.1182/blood-2003-07-2427
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic gene activation by lipopolysaccharide in macrophages: implication of hypoxia-inducible factor 1α

Abstract: Hypoxia-inducible factor 1 (HIF-1) regulates many genes induced by low oxygen conditions. The expression of important hypoxic genes such as glucose transporter 1 and vascular endothelial growth factor are increased in macrophages during wound healing and in the presence of the endotoxin, lipopolysaccharide (LPS). Recent studies have demonstrated that nonhypoxic stimuli can also activate HIF-1 in a cell-specific manner. Here, we demonstrate that in macrophages, LPS can control the activation of hypoxia-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
333
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(365 citation statements)
references
References 50 publications
(82 reference statements)
21
333
1
6
Order By: Relevance
“…VE-PTP not only dephos- it is known that HIFs are stabilized in response to endotoxin in macrophages (46) and that mitochondrial ROS generation in ECs contributes to HIF activation (47,48). This is especially important for the translational relevance of these findings, because they suggest that HIF2α is a potential therapeutic target in sepsis before the onset of severe pulmonary edema and hypoxemia.…”
Section: Discussionmentioning
confidence: 96%
“…VE-PTP not only dephos- it is known that HIFs are stabilized in response to endotoxin in macrophages (46) and that mitochondrial ROS generation in ECs contributes to HIF activation (47,48). This is especially important for the translational relevance of these findings, because they suggest that HIF2α is a potential therapeutic target in sepsis before the onset of severe pulmonary edema and hypoxemia.…”
Section: Discussionmentioning
confidence: 96%
“…However, this is not the case in human peripheral blood T cells (22). Moreover, it is reported that, in monocyte/macrophage, lipopolysaccharides enhance HIF-1␣ expression via increased expression of HIF-1␣ mRNA (15). Hudson et al (33) showed that rapamycin interferes with HIF-1␣ activation in hypoxic PC-3 cells by increasing the rate of HIF-1␣ degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this hypoxia-dependent mechanism, recent studies have demonstrated non-hypoxic pathways for regulation of HIF-1␣ activity (9,10) and multiple regulatory mechanisms of HIF-1␣ protein level, may enable cells to adapt to diverse alteration of environments and preserve homeostasis in a tissue-dependent manner. For example, receptor-mediated regulation of HIF-1␣ expression is thought to be cell and signal specific, and a number of reports have suggested that receptor-mediated factors such as growth factors, hormones, and cytokines induce HIF-1␣ protein expression through various signalings including PI3K/mammalian target of rapamycin (mTOR) pathway (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Induce HIF-1␣ Expression-Previous studies from our group (24) and others (27,28) indicated that Gram-negative bacterial cell wall components such as lipopolysaccharide induce HIF-1␣ expression in myeloid cells. To determine whether a parallel effect occurred with Gram-positive wall components, we examined whether HIF-1␣ transcriptional activity is modulated by exposure of macrophages to Gram-positive bacteria such as S. aureus.…”
Section: Gram-positive Bacteria Wall Components Transcriptionallymentioning
confidence: 99%